2014
DOI: 10.1095/biolreprod.114.117531
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Uterine Transcriptome, Responsive to Steroid Receptor Coactivator-2, Reveals Transcription Factor 23 as Essential for Decidualization of Human Endometrial Stromal Cells1

Abstract: Recent data from human and mouse studies strongly support an indispensable role for steroid receptor coactivator-2 (SRC-2)-a member of the p160/SRC family of coregulators-in progesterone-dependent endometrial stromal cell decidualization, an essential cellular transformation process that regulates invasion of the developing embryo into the maternal compartment. To identify the key progesterone-induced transcriptional changes that are dependent on SRC-2 and required for endometrial decidualization, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…As further support for this conclusion, immunohistochemical analysis of human endometrial biopsy samples show that PLZF protein is highly expressed in the nucleus of the endometrial stromal cell during the P4-dominant secretory phase of the menstrual cycle but is expressed at low levels in endometrial tissue biopsied during the E2-dominant proliferative phase of the cycle ( Fig 1D–1F ). In the uterus of the ovariectomized mouse, Plzf transcript and protein levels are also significantly and rapidly induced by P4 ( S2 Fig ), validating our previous microarray analysis of this tissue which showed Plzf transcription is induced by short-term P4 exposure [ 9 ]. Transcript and protein levels for Plzf were detected as early as six hours following P4 administration ( S2A and S2B Fig ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…As further support for this conclusion, immunohistochemical analysis of human endometrial biopsy samples show that PLZF protein is highly expressed in the nucleus of the endometrial stromal cell during the P4-dominant secretory phase of the menstrual cycle but is expressed at low levels in endometrial tissue biopsied during the E2-dominant proliferative phase of the cycle ( Fig 1D–1F ). In the uterus of the ovariectomized mouse, Plzf transcript and protein levels are also significantly and rapidly induced by P4 ( S2 Fig ), validating our previous microarray analysis of this tissue which showed Plzf transcription is induced by short-term P4 exposure [ 9 ]. Transcript and protein levels for Plzf were detected as early as six hours following P4 administration ( S2A and S2B Fig ).…”
Section: Resultssupporting
confidence: 85%
“…Comparing undecidualized hESCs with decidualized hESCs in culture, we recently revealed by RNA-seq analysis that PLZF (also known as ZBTB 16 , a Kruppel C2H2-type zinc-finger transcription factor) is listed in the top 20 genes which are significantly induced in hESCs during decidualization [ 8 ] ( S1A Fig ). Additionally, we previously showed by microarray analysis that Plzf is present in the top 100 genes induced in total uterine tissue of the mouse in response to acute P4 administration [ 9 ], suggesting PLZF is a P4-responsive gene and important for decidualization. To address this proposal, an established cell culture-based model for decidualization of primary hESCs was used to determine the transcriptional induction profile of PLZF ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cultures of human endometrial stromal fibroblasts (hESCs) have the ability to undergo in vitro decidualization, and this culture system has been used to demonstrate the importance of several factors in uterine decidualization, such as LIF [ 84 ], transient receptor potential cation channel, subfamily C, member 1 ( TRPC1 ) [ 85 ], transcription factor 23 ( TCF23 ) [ 86 ], uterine activing like kinase 2 (ALK2) [ 78 ], bone morphogenetic protein 2 ( BMP2 ) [ 87 ], and WNT4 [ 88 ]. Previous work has shown that ARID1A is deficient in hESCs from women with endometriosis [ 21 ] and that in vitro decidualization of hESCs from women with endometriosis have a blunted in vitro decidualization response [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…4) Apart from PFKFB3 induction, does SRC-2 coregulate other progesterone signaling pathways that are important for ESC decidualization? In the case of the mouse at least, recent microarray array studies reveal that SRC-2 is critically important for the full induction of the majority of previously known molecular mediators of progesterone-driven ESC decidualization [110]. Whether these findings can be translated to the human ESC remains an open question.…”
Section: Metabolic Reprogramming By Src-2 Underpins Endometrial Decidmentioning
confidence: 99%